A finite-strain homogenization model for viscoplastic porous single crystals: II – Applications. (October 2017) - Song, Dawei; Ponte Castañeda, P.
Abstract: In part I of this work (Song and Ponte Castañeda, 2017a), a new homogenization-based constitutive model was developed for the finite-strain, macroscopic response of porous viscoplastic single crystals. In this second part, the new model is first used to investigate the instantaneous response and the evolution of the microstructure for porous FCC single crystals for a wide range of loading conditions. The loading orientation, Lode angle and stress triaxiality are found to have significant effects on the evolution of porosity and average void shape, which play crucial roles in determining the overall hardening/softening behavior of porous single crystals. The predictions of the model are found to be in fairly good agreement with numerical simulations available from the literature for all loadings considered, especially for low triaxiality conditions. The model is then used to investigate the strong effect of crystal anisotropy on the instantaneous response and the evolution of the microstructure for porous HCP single crystals. For uniaxial tension and compression, the overall hardening/softening behavior of porous HCP crystals is found to be controlled mostly by the evolution of void shape, and not so much by the evolution of porosity. In particular, porous HCP crystals exhibit overall hardening behavior with increasing porosity, while they exhibit overall softening behavior with decreasing porosity. This interesting behavior is consistent with corresponding results for porous FCC crystals, but is found to be more significant for porous HCP crystals with large anisotropy, such as porous ice, where the non-basal slip systems are much harder than the basal systems.